Analysis Of Roof Bolt Systems (80829435-dd55-4b61-96dd-df38d097e9ff) - Christopher Mark (International Conference on Ground Control in Mining, 2001)
Despite more than half a century of experience with roof bolting, no design method has received wide acceptance. To begin to improve this situation, National Institute for Occupational Safety and Health (NIOSH) conducted a statistical study of roof bolt performance at a number of mines throughout the U.S. Case histories were collected from 37 mines with a variety of roof bolt types and patterns in a wide range of geologic environments. Performance was measured in terms of the number of roof falls that occurred per 10,000 ft of drivage. The study found that roof falls are rare when the roof is strong and the stress is low, even with light roof bolting patterns. The focus of this paper is on the more difficult conditions, where the roof is weaker and/or the stress is higher. Analysis of the results led to guidelines that can be used to make preliminary estimates of the required bolt length, capacity, and pattern. The guidelines are based on the depth of cover (which correlates with stress) and the roof quality (measured by the Coal Mine Roof Rating (CMRR), and the intersection span. Another contribution is a formula for estimating the horizontal stress level in the eastern U.S. coalfields as a function of the depth of cover. The design guidelines are currently being implemented into a computer program called Analysis of Roof Bolt Systems (ARBS).